Edukacja środowiskowa w zadaniach rodziny - Irena Grochowska (Studia Ecologiae et Bioethicae)
Solutions to such an important problem as an ecological crisis should be sought to start with indicating reasons for such a situation. Contamination of the environment, using up the natural resources, changes in biodiversity of flora and fauna, and many other similar urgent problems are the effects of actions that lead to family, social, political, or economical structures, or also lack of specified aim or sense in life, the basis for all these structures is nevertheless the family and it can be easily said the family crisis is the beginning of the crisis in other areas of human life also an ecological crisis. It is important in bringing up and environmental education to prepare for coexistence with nature and to respect humans’ habitat. Creative companionship with young people in the road which they should take from the moment of conception to the moment of achieving an integrated personality, such that in the practice of everyday life he would realize through his motivated posture “mature ecological outlook on life“ starts with the family and cooperation with others. Personal growing up of human beings takes place not in isolation but in cooperation with others.